Hubungan Peer Tutoring dengan Nilai Keaktifan Tutorial pada Mahasiswa Fakultas Kedokteran Universitas Islam Indonesia Angkatan 2015 - Yanasta Yudo Pratama; Yeny Dyah Cahyaningrum; Titis Nurmasitoh (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: The method to improve learning achievement is peer tutoring method. Students can grow and increase their interest in learning, so that the learning materials in the tutorial can be easily understood. By increasing student interest in learning, student learning success will be achieved. The problem raised in this study is how the peer tutoring method influences the results of tutorial activeness.Research Objectives: Knowing the participation of peer tutoring on the value of the activity of the “Blok Masalah Pada Anak” tutorial on the students of Faculty of Medicine UII Force 2015.Methods: The experiments were quasi experimental research. This research design uses posttest only with control design. A total of 40 research subjects came from 2 different groups. The ratio of the control group to the treatment group was 1: 1. The control group was a group that was not given peer tutoring and the treatment group was a group given peer tutoring. Data analysis using Independent T Test.Results: There was no difference in scores of scenario 6 activation score in the control group and treatment group with p value 0.704 and 95% CI interval between -9.79 to 4.79 (past 0.)Conclusion: There is no relationship of peer tutoring with the score of the activity of tutorial block Problems In Children at the Faculty of Medicine, Universitas Islam Indonesia batch 2015.